The Role of Peers in Shaping Purchasing Decisions of Fashion Products among Teenagers - Bahari, Winona Monica; Nabila, Aisyah Putri; Budiarto, Chris Louis; Hidayat, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2025)
This study explores the influence of the social environment on consumer decision-making patterns among teenagers. This research uses a qualitative, descriptive approach and a literature study. The results showed that the social climate significantly influences adolescent consumer decision-making patterns. These findings can help understand how the social environment affects adolescent consumer behavior and contribute to developing effective marketing strategies; keywords: social environment, consumer decision-making patterns, adolescents, qualitative approach, and literature study.